Conexões em sala de aula: uma análise das interações sociais no ensino médio em situações de uso pedagógico ou de proibições dos smartphones - Flávia Aparecida Belizário (2018)
Access to digital technological artifacts has been changing life in society, and it has also permeated school reality. Such changes bring questions to the field of Sociology of Education, for example, the need to understand the implications of digital technologies in the students and teachers activities, regarding the interactions they establish among themselves, the uses that make these technologies within the school and the impacts on school inequalities. This work specifically focuses on the smartphone, which has occupied centrality in the daily life of high school students, but is generally banned in classrooms, being used just in a few cases by teachers as a pedagogical tool. We sought to analyze how the interactions in the classroom are constructed, between students and among them and their teachers, mediated by the use of smartphones. We investigated the perspectives of the different subjects for the use of these devices, the strategies and negotiations that develop around them and the perception of the actors as to the effectiveness or not of the educational use of smartphones. The adopted theoretical framework was the sociology of the classroom, mobilizing interactionist analytical instruments such as social roles, student work, perspectives, strategies and negotiations. A research was carried out in a public school in the metropolitan area of Belo Horizonte (MG), in two first grade of high school classrooms, focusing on the disciplines of Physics, in which the smartphone was used as a pedagogical tool, and Biology, in which the students smartphone use was prohibited. Observations of the classes of these disciplines were made during the first semester of 2017; a questionnaire was applied to all students in both rooms and, finally, semi-structured interviews were conducted with the two teachers and with 14 students, seven of each class. The collected data confirmed the importance of considering the contemporary juvenile subjectivities in the understanding of the way in which young people exercise their students office, as well as the relevance of smartphones as influential artifacts in the construction of these subjectivities. They also revealed that, according to the perception of the interviewed students and teachers, the use of cell phones as a pedagogical tool contributes to the attractiveness of the classes. The results evidenced, above all, the centrality of the teaching activity in the mediation of the interactions in the classroom, indicating that the most decisive were the teachers strategies. It was found that both teachers could be considered effective in negotiating the meaning of the proposed activities - evidently, within the limits of school play - and provoke the mobilization of the majority of students around them.